BekasMart: Marketplace C2C Berbasis Web dengan Fitur Lelang dan Penjualan Langsung - Nafil Rizq Trianto; Azril Arfansyah; Arion Pardede; Debi Yandra Niska (Universitas Merdeka Malang, 2026)
Customer to Customer (C2C) transactions on social media were often hindered by manual bid recapitulation and bid-and-run fraud risks due to the absence of an integrated platform. This study designed and developed a web-based C2C marketplace information system named BekasMart, integrating direct sales and auction features using a Guest System architecture. The Waterfall method was applied, covering requirements analysis, system design using Unified Modeling Language (UML), implementation with the CodeIgniter 4 framework, and Black Box Testing. Results demonstrated that the Guest System architecture, based on WhatsApp number validation, successfully facilitated transactions without conventional login bureaucracy. Transaction security was maintained through an Escrow (Rekber) mechanism and WhatsApp Direct Link integration. Functional testing confirmed the system processed bids automatically with a 100% success rate.